Perubahan Pola Interaksi Keluarga Akibat Penggunaan Media Sosial pada Masyarakat Kota Medan - Muhammad Ridho’i; Naila Isnani; Tatiya Rambe; Karina Amelia; Galih Rizqy Ananda; Rholand Muary (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The development of social media as part of digital technology advancements has brought significant changes to family interaction patterns, particularly in urban communities with high levels of social media use. This study aims to analyze changes in family interaction patterns due to social media use in Medan, identify the positive and negative impacts, and examine the efforts families make to maintain the quality of interactions. The study used qualitative methods with a descriptive approach. Data were collected through observation, semi-structured interviews, and documentation with informants who actively use social media in their daily lives. The results indicate that social media use has shifted family communication patterns from one dominated by face-to-face interactions to digital-based communication. These changes have positive impacts in the form of ease of communication, faster information exchange, and the maintenance of family relationships even when living apart. However, excessive social media use also has the potential to reduce the intensity of direct communication, decrease the quality of interactions, and diminish emotional closeness between family members. Therefore, wise management of social media use is necessary by increasing direct communication, limiting device use, and strengthening openness within the family to maintain the quality of family relationships in the digital era.